Colorectal cancer progression is potently reduced by a glucose-free, high-protein diet: comparison to anti-EGFR therapy - Skibbe, Kerstin; Ann-Kathrin Brethack; Suenderhauf, Annika; Ragab, Mohab; Raschdorf, Annika; Hicken, Maren; Schlichting, Heidi; Preira, Joyce; Brandt, Jennifer; Castven, Darko; Foeh, Bandik; Pagel, Rene; et al. (bioRxiv, 2021)
Background & Aims: To enable rapid proliferation, colorectal tumor cells up-regulate epidermal growth factor receptor (EGFR) signaling and perform high level of aerobic glycolysis, resulting in substantial lactate release into the tumor microenvironment and impaired anti-tumor immune responses. We hypothesized that an optimized nutritional intervention designed to reduce aerobic glycolysis of tumor cells may boost EGFR-directed antibody (Ab)-based therapy of pre-existing colitis-driven colorectal carcinoma (CRC). Methods: CRC development was induced by azoxymethane (AOM) and dextran sodium sulfate (DSS) administration to C57BL/6 mice. AOM/DSS treated mice were fed a glucose-free, high-protein diet (GFHPD) or an isoenergetic control diet (CD) in the presence or absence of i.p. injection of PBS, an irrelevant control mIgG2a or an anti-EGFR mIgG2a. Ex vivo, health status, tumor load, metabolism, colonic epithelial cell differentiation and immune cell infiltration were studied. Functional validation was performed in murine and human CRC cell lines MC-38 or HT29-MTX. Results: AOM/DSS treated mice on GFHPD displayed reduced systemic glycolysis, resulting in improved tumoral energy homeostasis and diminished tumor load. Comparable but not additive to an anti-EGFR-Ab therapy, GFHPD was accompanied by enhanced tumoral differentiation and decreased colonic PD-L1 and splenic PD-1 immune checkpoint expression, presumably promoting intestinal barrier function and improved anti-tumor immune responses. In vitro, glucose-free, high-amino acid culture conditions reduced proliferation but improved differentiation of CRC cells in combination with down-regulation of PD-L1 expression. Conclusion: We here found GFHPD to metabolically reprogram colorectal tumors towards balanced OXPHOS, thereby improving anti-tumor T-cell responses and reducing CRC progression with a similar efficacy as EGFR-directed antibody therapy. Competing Interest Statement The authors have declared no competing interest.